Transthoracic discectomy for a rare presentation of calcified dorsal disc herniation - Chauhan, Lokendra Singh; Tak, Mahendra Singh; Suthar, Lakshit; Shreyas, C. S. (International Journal of Research in Orthopaedics, 2025)
Thoracic disc herniation is rare entity, with incidence of 0.5%-4% of all disc herniation. Mostly are asymptomatic and does not need treatment if symptomatic cause intractable pain, intercostal neuralgia, persistent axial back pain and myelopathic symptom need surgical excision. We present a case of 74-year female with central calcified dorsal disc herniation at T11-12 level. surgical excision done by transthoracic discectomy.